2014
DOI: 10.11613/bm.2014.041
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia modified albumin is an indicator of oxidative stress in multiple sclerosis

Abstract: Introduction:Oligodendrocytes need iron in processes of energy generation and myelination. However, excessive levels of iron may exert iron induced oxidative stress and thus lead to tissue degeneration. Monitoring oxidative stress will be of paramount importance in follow-up of patients with many diseases including multiple sclerosis (MS). The aim of this study was to measure total anti-oxidative status (TAS), total oxidative status (TOS) and ischemia modified albumin (IMA) in stable relapse remitting MS (RRMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…IMA levels have been reported to increase in diseases capable of causing acute or chronic hypoxia and oxidative stress 17 . IMA levels also increase in diseases that oxidative stress is implicated in etiopathogenesis, such as psoriasis, diabetes mellitus, multiple sclerosis, some cancers, polycystic ovary syndrome and b-thalassemia major 10,[18][19][20][21][22] . Our review of the literature revealed a limited number of studies of IMA and dermatological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…IMA levels have been reported to increase in diseases capable of causing acute or chronic hypoxia and oxidative stress 17 . IMA levels also increase in diseases that oxidative stress is implicated in etiopathogenesis, such as psoriasis, diabetes mellitus, multiple sclerosis, some cancers, polycystic ovary syndrome and b-thalassemia major 10,[18][19][20][21][22] . Our review of the literature revealed a limited number of studies of IMA and dermatological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The advances in disease monitoring and treatment are promising with respect to decelerating the progression of disabilities. Current understanding of the fundamental nature of MS is limited, and future goals are directed towards better disease management and repair of injured CNS tissue [1,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicate that oxidative stress has a major role in the etiology of MS 14. In addition, ischemia modified albumin, a highly sensitive marker for ischemia, is elevated in MS patients 15. In another study, correction of chronic hypoxia with full CBAP treatment resulted in a reduction in inflammation and decreased expression of some inflammatory markers 16.…”
Section: Discussionmentioning
confidence: 95%